Assessment of augmented reality mobile application for educational purposes / Amirul Afiq Jamaluddin ... [et al.] - Jamaluddin, Amirul Afiq; Rusli, Noradila; Yoke, Lai Lee; Hoh, Gabriel Teck Ling (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Augmented Reality (AR) is among the advanced technology accessible worldwide, which constantly noticeable in the entertainment industry. However, there is no universal nor accessible augmented reality to be found offering in Malaysia higher education. This research intends to apply augmented reality application within an educational perspective and evaluate its effectiveness based on four (4) criteria that comprises: performance, usefulness, learnability, and accuracy. An augmented reality application, Floristic was developed to cooperative in teaching plant material at Tropical Park of Universiti Teknologi Malaysia (UTM), Skudai. A pilot study has conducted within a limited period where the participants had responded to collect and evaluate several flora species using the median score system. Based on the results, the Floristic 'performance' scored four (4) out of five (5), the 'usefulness' scored five (5), the 'learning skill' 4.8, and the 'accuracy' scored four (4). Meanwhile, the questionnaires survey was analysed as a recommendation for further improvement. In conclusion, the implementation of augmented reality for teaching and learning purposes will make the learning process more engaging and exciting. AR technology is also very fast-growing, and there seems to be a great deal of potential in the use of augmented reality rather than in the choice of floral identification alone.